A four-year cycle comparison of the nutritional and cardiovascular health status of an elite-level female artistic gymnast: case study report from slovenia - Jakše, B.; Jakše, B. (Science of Gymnastics Journal, 2023)
Regular monitoring of body composition, nutrition, health, and motor skills are crucial for further training process planning and performance progress. With the same protocol and methods, we evaluated a four-year change (2018 vs. 2022) in the nutritional and cardiovascular health status of the currently most successful elite-level adult female artistic gymnast in Slovenia. Detailed body composition and dietary intake were assessed using dual-energy X-ray absorptiometry and a standardized food questionnaire FFQ. The blood lipids and safety factors, blood pressure, and serum micronutrients (e.g., B12, 25-hydroxyvitamin D (25(OH)D), potassium, calcium, phosphorus, magnesium, and iron) status were measured. The four-year comparison showed an improved body composition status: decreased body fat mass/percentage, android fat percentage, and android/gynoid ratio, while other anthropometrical and body composition parameters remained essentially unchanged. We also measured an improvement of some and worsening of other cardiovascular health serum variables (i.e., decreased total cholesterol but increased low-density lipoprotein cholesterol and S-glucose), most likely due to the differences in assessed dietary intake (i.e., lower total fat, mono- and polyunsaturated fatty acid intake but higher cholesterol intake and still high free sugar and saturated fat intake, despite higher fiber). Notably, nutrient intakes that are generally of concern (fiber (borderline low intake), eicosapentaenoic omega-3 fatty acids and docosahexaenoic omega-3 fatty acids, vitamin B12 and D, calcium (borderline low intake), iron, and zinc) were within recommended ranges. However, the athlete`s vitamin E and potassium intakes were not adequate. Furthermore, in 2018, the athlete did not consume dietary supplements, while she now regularly uses several dietary supplements, including enriched plant-based protein powder, isolated vitamin B12, C, D, and iron. Moreover, the athlete had significantly lower than recommended serum levels of 25(OH)D, probably due to insufficient regular intake of vitamin D in the form of a dietary supplement (1000 IU/d). Moreover, from the micronutrient serum, phosphorus, and iron levels that deviated from the reference values in the 2018 study, in the current study, they were found to be within referenced ranges (i.e., iron status was markedly improved). This kind of screening toolbox, using valid, sensitive, and affordable methods and with rapid organizational implementation, may be a viable format for regular monitoring.